KONSEP KOREOGRAFI BEDAYA HERJUNA WIWAHA - Kristiyanti, Dewi (Acintya, 2018)
This research is entitled A Choreography Concept of Bedaya Harjuna Wiwaha Dance. The Yogyakarta style of Bedaya Harjuna Wiwaha dance was composed by KRT Sasmintadipuro performed in Tingalan Dalem Sri Sultan Hamengku Buwana IX in 1976. In Bedaya Harjuna Wiwaha dance, all dancers have their respective roles. The role of the dancers in Bedaya Harjuna Wiwaha dance is like the other Bedaya dance. The roles of the dancers includeEndhel Pajeg, Batak, Jangga, Dhadha, Buntil, Apit Ngajeng, Apit Wingking, Endhel Wedalan Ngajeng and Endhel Wedalan Wingking. Some of these roles represent characters in the story contained in Bedaya Harjuna Wiwaha dance, such as Prabu Newatakwaca, Harjuna and Dewi Supraba. In addition, norms or rules for the arrangement of Bedaya Harjuna Wiwaha dance include: rules for the use and application of dance motives, rules for the use and application of floor patterns, rules for the use of rhythm of motion, story sources, dance forms and dance styles . Keywords: Choreography Concept, Bedaya Herjuna Wiwaha